Students' perceived predictors of an effective active learning/problem‐based learning session: a pilot study. (March 2016) - Jacob, Sabrina A.; Khan, Tahir M.; Pusparajah, Priyia; Velu, Saraswati S.; Lee, Learn Han; Davey, Tamzyn M.
Abstract : Abstract : Active learning (AL)/problem‐based learning (PBL) has been shown to improve the reasoning, communication and team‐work skills of students. However, the success of AL/PBL tends to vary depending on local context and culture. We undertook a study to assess pharmacy students' current experience, expectations and level of understanding of AL/PBL. A focus group discussion involving ten Year‐4 pharmacy students was conducted in Malaysia. Three key themes emerged: expectations of the AL/PBL session, tutor characteristics and cultural issues. The students expected that the AL/PBL session should help them apply their knowledge in real‐life clinical situations. They also felt that the personality of the tutor was the key to the success of AL/PBL, and that Asians were more hesitant to participate in AL/PBL sessions. AL/PBL has the potential to be effective provided the sessions are carefully planned, and tutors are well trained in the context of local culture.